Treatment Outcomes and Associated Factors in Tuberculosis Patients at Atwima Nwabiagya District, Ashanti Region, Ghana: A Ten-Year Retrospective Study - Agyare, Sadick Ahmed (Tuberc Res Treat, 2021)
INTRODUCTION: Tuberculosis poses a great threat to public health around the globe and affects persons mostly in their productive age, notwithstanding; everyone is susceptible to tuberculosis (TB) infection. To assess the effectiveness and performance of the tuberculosis control program activities, the percentage of cases with treatment success outcome is key. To control tuberculosis, interrupting transmission through effective treatment cannot be overemphasized. The study was conducted to determine factors associated with TB treatment outcome, in the Atwima Nwabiagya District from 2007–2017. METHOD: A Retrospective review of routine/standard TB registers was carried out in five directly observed therapy short-course (DOTS) centres at the Atwima Nwabiagya District from January 2007 to December 2017. Demographic characteristics, clinical characteristics, and treatment outcomes were assessed. Bivariate and multivariate logistic regression was conducted to determine the predictors of successful treatment outcome. RESULTS: Of the 891 TB client's data that was assessed in the district, the treatment success rate was 68.46%. Patients, aged ≤ 20 years (adjusted odds ratio (aOR) = 4.74, 95%CI = 1.75 − 12.83) and 51-60 years (aOR = 1.94, 95%CI = 1.12 − 3.39), having a pretreatment weight of 35-45 kg (aOR = 2.54, 95%CI = 1.32 − 4.87), 46-55 kg (aOR = 2.75, 95%CI = 1.44 − 5.27) and 56-65 kg (aOR = 3.04, 95%CI = 1.50 − 6.14) were associated with treatment success. However, retreatment patients (aOR = 0.31, 95%CI = 0.11 − 0.84) resulted in unsuccessful treatment outcome. CONCLUSION: Successful treatment outcome among TB patients was about 20.00% and 30.00% lower compared to the national average treatment success rate and WHO target, respectively. Active monitoring, motivation, and counselling of retreatment patients and patients with advanced age are key to treatment success.